Efficacy and safety of various regional nerve blocks for postoperative analgesia in paediatric patients undergoing developmental dysplasia of the hip surgery: a protocol for systematic review and network meta-analysis - Lei Yang; Yu Zhang; Chen Fu; Wang Junxia; Zhijun Qin (BMJ Open)
Introduction Alleviating postoperative pain from developmental dysplasia of the hip (DDH) surgery is beneficial for paediatric patients. The most commonly used anaesthetic approach currently is general anaesthesia combined with regional nerve blocks. Existing research primarily focuses on studies comparing regional nerve blocks with placebo controls, or studies comparing two different regional nerve blocking techniques. However, the conclusions from these studies offer limited assistance to clinicians in selecting the safest and most effective nerve block. Therefore, we plan to conduct a systematic review and network meta-analysis to compare the efficacy and safety of different regional nerve blocks in managing postoperative pain in children undergoing surgery for DDH.Methods and analysis We will systematically search the following databases: MEDLINE, Embase, Cochrane Central Register of Controlled Trials via Ovid, as well as the Chinese databases CNKI and Wanfang. We will comprehensively search from the inception of each database to April 2024 and will include randomised controlled trials without restrictions on language or publication status. The primary outcome are postoperative pain scores at 4 hours following surgery. The quality of all included trials will be assessed using version 2 of the Cochrane Randomised Trial Risk of Bias Tool. We will employ the GeMTC package in R software for both direct and indirect comparisons within a Bayesian framework using a random effects model. Additionally, the Confidence in Network Meta-Analysis method will be employed to assess the quality of evidence.Ethics and dissemination Ethical approval is not required for this study, as it exclusively involves the compilation of published data. We plan to submit our review to academic conferences and peer-reviewed scholarly journals.PROSPERO registration number CRD42024527459.